Daylighting Using Tubular Light Guide Systems - Callow, Joel Morrison (2003)
The reduction of fossil fuel consumption and the associated decrease in greenhouse gas emissions are vital to combat global warming and this can be accomplished, in part, by the use of natural light to provide illumination in buildings. Demand for artificial lighting and the availability of daylight often correspond, so savings can be significant. To assess the performance of several innovative daylighting devices and to develop improved models for more established technology, quantitative measurement of output was necessary. This was achieved by the development of simply constructed photometric integrators which were calibrated by the innovative use of daylight as a source of illuminance. These devices were found to be consistent and accurate in measuring the luminous flux from a number of devices and in a number of locations. The novel light rod was assessed as a core daylighting technology and found to transmit light with high efficiency at aspect ratios of up to 40. It was found to have higher transmittance than the light pipe and with a considerably smaller diameter, could be used in space-restricted applications. Light rods were bent by infra-red heating and found to lose minimal transmittance. The light rod emitter was modified to give a variety of types of light distribution, including side emission and the results were visually and quantitatively assessed. Energy saving capacity was assessed and a model of performance developed for the first time. The long-term measurement of light pipe performance and measurement of length and diameter effects led to several improved models of performance for European latitudes. Several means of improving yield were investigated, including novel cone concentrators, laser cut panels and innovative high-efficiency reflective films. The concentrators and films were found to give significantly higher output than a standard light pipe, increasing energy savings and associated benefits for the user.